Telling narratives : secrets in African American literature - Lewis, Leslie W., 1960- (Urbana : University of Illinois Press, 2007)
"Telling Narratives analyzes key texts from nineteenth- and early-twentieth-century African American literature to demonstrate how secrets and their many tellings have become slavery's legacy. This study focuses on the ways secrets are told in abolitionist texts and in novels of uplift, including those by William Wells Brown, Jessie Fauset, Charles W Chesnutt, Martin Delany, Frances E.W. Harper, Pauline Hopkins, James Weldon Johnson, and Frederick Douglass. In examining how racial and sexual secrets are kept and told in these works, Leslie W. Lewis traces how interaction between masters and female slaves became central to a developing African American literary tradition." "While stressing that secrets are muted articulations, Lewis suggests an alternative model to the feminist dichotomy of "breaking silence" in response to sexual violence. She argues that secretive information gave female slaves agency because they could choose whether or not to disclose or reveal their knowledge. This study also highlights the ways that masculine bias problematically ignores female experience in order to equate slavery with social death. In calling attention to the sexual behavior of slave masters in African American literature, Lewis highlights its importance to slavery's legacy and offers a new understanding of the origins of self-consciousness within African American experience."--Jacket.
Introduction: Positioning Secrets -- The Master/Female Slave Moment as Slavery's Legacy -- Father/Son Relations in African American Abolitionist Fiction -- Slave Mothers and Colored Consciousness -- Narrative Fathering and the Epistemology of Secret Knowing -- Queering America's Family: Jessie Fauset's Modern Novels -- Afterword: Telling in the Twentieth Century.
Includes bibliographical references (pages 199-212) and index.
JSTOR
Keywords: American literature -- African American authors -- History and criticism; African Americans in literature; Noirs américains dans la littérature.; African Americans in literature; American literature -- African American authors; LITERARY CRITICISM / General; Criticism, interpretation, etc